Congenital and acquired diseases related to stone formation. Issue 5 (September 2018) - Veser, Julian; Özsoy, Mehmet; Seitz, Christian
Abstract : Purpose of review: To summarize the latest findings of congenital and acquired diseases related to stone formation and help understanding the multitude of cofactors related to urolithiasis. Recent findings: Urolithiasis is related to a broad spectrum of congenital and acquired diseases and its management varies according to the stone type, underlying disease or recurrence rate, but it also changes according to recent findings and developments. As prevalence of urolithiasis is constantly increasing, identification of high-risk stone formers and early treatment is essential. Therefore, genetic evaluation like whole exome sequencing becomes a pertinent part of further diagnostics. Summary: Stone formation is a very heterogeneous pathomechanism. This prompt us to look at every patient individually particularly in high-risk patients, including stone and 24-h-urine analysis and additional diagnostic work-up based on stone type or underlying disease.